Administration of prostaglandin to beef heifers at time of artificial insemination - Johnson, Sandra K.; Jaeger, John R. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2014)
Transportation of sperm is a critical component of reproductive success. Another factor in reproductive success are the contractions of the uterine myometrium, which influence the number of sperm that reach the oviduct. Prostaglandin F2α (PG) is present in bull semen and has a variety of functions in reproduction, including stimulating myometrial contractions. Evidence of improved fertility after administration of PG at breeding has been shown in the rabbit, sow, and cow. An injection of PG at the time of insemination improved conception rates in heifers inseminated with semen with only 30% motility. The objective of the study was to determine if administration of prostaglandin F2α at the time of insemination would improve pregnancy rate to artificial insemination (AI) when insemination occurred after observed estrus or at fixed-time insemination.
Keywords: Beef; Artificial insemination; Fertility; Prostaglandin